Management and Sustainable Development of Coastal Zone Environments - Ramanathan, A L.; Bhattacharya, P.; Dittmar, T.; Prasad, M. Bala Krishna; Neupane, B. R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Coastal areas face increasing pressures from land use change, developmental activities, shoreline erosion, biodiversity losses and natural calamities. This volume addresses these issues facilitating the integrated analysis of the sustainability of coastal zones. The contributors have tried to focus their respective works on the problems that need urgent attention relevant to present day issues. Coastal Zone Management and its sustainability strategy should safeguard ecological security of the coastal areas, avoid pollution as well as exploitation of living and non living aquatic resources, protecting also the agrarian community and avian population and other floral and faunal breeding grounds. Articles have been selected on the basis of sound scientific findings hoping that it will help in developing meaningful regulations for future sustainable coastal management zone.
Evaluation, Status Prediction, Modelling and Developments of Coastal Zones: Management Issues -- Observational Needs for Sustainable Coastal Prediction and Management -- Ecological Modelling as a Tool for Coastal Ecosystem Management -- Current Status of Coastal Zone Management Practices in India -- Climate Resilient Coastal Zone Development in Bangladesh: Participatory Governance for Common Resources Management -- Present Status, Challenges and Management of the Japanese Coastal Zone Environment -- Integrating Hydrologic and Hydrodynamic Models for Decision Support Systems and Management of Coastal Zones and Estuaries -- Creation of System (3z(BDelta-Sea(3y (Bas a Basis of Ecosystem Approach to the Management of Large Aral Sea$1 (Bs Coastal Zone -- Coastal Zone Water Resources (Quantity and Quality): Challenges for Sustainability -- Critical Evaluation of the Recent Development and Trends in Submarine Groundwater Discharge Research in Asia -- Influence of Climate Factors on the Groundwater Resources of Coastal Tamilnadu -- Natural Arsenic in Coastal Groundwaters in the Bengal Delta Region in West Bengal, India -- Chemical Composition and Origin of the Coastal Zone Thermal Springs in Far East Russia -- Biodiversity of Coastal Zones and Its Sustainability -- Organic Matter and Mangrove Productivity -- Influence of Terrestrial Inputs on Mangrove and Coral Reef: Primary Productivity of the Andaman Islands -- Dissolved Metal Distribution in Indian Mangrove Ecosystem: Case Studies from East Coast of India -- Threats to Coastal Aquatic Ecosystems: Developmental and Sustainability Issues -- Shrimp Culture: Trend, Consequences and Sustainability in the South-western Coastal Region of Bangladesh -- Role of Sand Dunes and Mangroves in the Mitigation of Coastal Hazards with Reference to 2004 Tsunami -- Assessment of Potential Health Risk through Arsenic Flow in Food Chain$1 (BA Study in Gangetic Delta of West Bengal.s
Keywords: Geography; Life sciences; Hydraulic engineering; Geology; Sustainable development; Environmental pollution; Earth Sciences; Coastal Sciences; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Biogeosciences; Sustainable Development; Hydrogeology